Quantitative analysis of metabolites in glucose metabolism in the aqueous humor of patients with central retinal vein occlusion. (February 2020) - Wei, Pinghui; He, Meiqin; Teng, He; Han, Guoge
Abstract: Quantitative analysis of aqueous humor (AH) was performed to investigate glucose metabolism in patients with central retinal vein occlusion (CRVO), and to explore metabolic changes after anti-vascular endothelial growth factor (VEGF) treatment. AH samples were collected from 35 patients. Participants diagnosed with CRVO (n = 15) were compared to participants who underwent cataract surgery (n = 20). Thirteen of the participants with CRVO received second-round anti-VEGF treatments. Ultra-high performance liquid chromatography tandem-mass spectrometry (UHPLC-MS/MS) was used to quantify metabolites of the AH. Central macular thickness (CMT) and retinal ganglion cell layer (RGC) thickness were measured using spectral-domain optical coherence tomography. Thirteen metabolites involved in glucose metabolism were identified. Among these metabolites, succinate, glutamate, and glutamine were significantly decreased for the CRVO group (p = 0.028, 0.009, and 0.017, respectively). The α -ketoglutarate/citrate (K/C) ratio had a significant positive correlation with glutamine levels for both control ( r  = 0.922, p < 0.001) and CRVO groups ( r  = 0.674, p = 0.006). A significant increase in lactate was observed after intravitreal anti-VEGF administration ( t  = 2.273, p = 0.045); the change in CMT was negatively correlated with this increase ( r  = −0.745, p = 0.003). The alteration of RGC thickness was negatively correlated with increases in both glutamine ( r  = −0.619, p = 0.024) and glucose ( r  = −0.754, p = 0.003). These results indicate that, compared to glucose metabolism, glutamine was significantly decreased in the AH of patients with CRVO, and may therefore serve as a potential target for CRVO therapy. The glycolytic pathway might be enhanced after intravitreal anti-VEGF injection, which is an important insight into CRVO pathophysiology. Highlights: Succinate, glutamate, and glutamine were significantly low in patients with CRVO. The α-ketoglutarate/citrate ratio was positively correlation with glutamine levels. Lactate levels increased significantly after intravitreal anti-VEGF administration. The change in CMT was negatively correlated with lactate increase. RGC thickness was negatively correlated with increased glucose and glutamine levels.